2017
DOI: 10.1186/s40798-017-0102-3
|View full text |Cite
|
Sign up to set email alerts
|

Exercise and the Cortisol Awakening Response: A Systematic Review

Abstract: BackgroundThe cortisol awakening response (CAR) has been used as a biomarker of stress response in a multitude of psychological investigations. While a myriad of biochemical responses have been proposed to monitor responses to exercise training, the use of CAR within the exercise and sports sciences is currently limited and is a potentially underutilized variable. Therefore, the purpose of this review was to collate studies that incorporate both exercise and CAR, in an effort to better understand (a) whether C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
47
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 84 publications
8
47
1
1
Order By: Relevance
“…Intense physical training can also blunt the cortisol response to submaximal exercise (82). Studies are mixed as to whether chronic exercise also blunts the cortisol awakening response (CAR); the effect may only be evident with large exercise workloads (2) within-subjects study design in recreational runners found a decrease in cortisol awakening response with greater exercise workload (3).…”
Section: Hpa and Sns Reactivitymentioning
confidence: 99%
“…Intense physical training can also blunt the cortisol response to submaximal exercise (82). Studies are mixed as to whether chronic exercise also blunts the cortisol awakening response (CAR); the effect may only be evident with large exercise workloads (2) within-subjects study design in recreational runners found a decrease in cortisol awakening response with greater exercise workload (3).…”
Section: Hpa and Sns Reactivitymentioning
confidence: 99%
“…There is limited research on how exercise acutely impacts the CAR. To date, studies which have examined the effect of acute exercise on the CAR have only investigated exercise performed during the evening (Garde et al, 2009;Anderson and Wideman, 2017;Ucar et al, 2018). These studies found that a single bout of exercise performed in the evening had no impact on the CAR (Garde et al, 2009;Ucar et al, 2018).…”
Section: During Exercisementioning
confidence: 99%
“…Despite the limited research on the effect of acute exercise on the CAR, some evidence suggests that acute exercise does affect circulating cortisol levels (Kindermann et al, 1982;Hill et al, 2008;Crewther et al, 2010;Anderson and Wideman, 2017). This is one of the reasons that it is recommended for study participants to remain sedentary when cortisol samples are obtained (Stalder et al, 2016).…”
Section: During Exercisementioning
confidence: 99%
See 1 more Smart Citation
“…The HPA axis may be another key mediating factor in the relation between exercise and depression. In a recent review, it was suggested that exercise can play a role in the cortisol awakening response (CAR), however, it seems that this effect was only apparent with higher frequencies of exercise (Anderson & Wideman, 2017). This finding may be particularly relevant, as the CAR is often broader among individuals who chronically perceived distress (Kaspers & Scholz, 2004).…”
Section: Exercise and Hpa Functioningmentioning
confidence: 99%